PEMANFAATAN TEKNOLOGI DIGITALISASI BISNIS DI BIDANG PEMASARAN, PRODUKSI DAN KEUANGAN UNTUK MENINGKATKAN OMSET PENJUALAN PADA UMKM DI DESA KARANG SARI, DIENG KULON, BATUR, BANJARNEGARA - Walid Rudianti; Ghonimah Ainiyah; Ratna Suryani (Unperba Press, 2026)
Micro, Small, and Medium Enterprises (MSMEs) make a substantial contribution to Indonesia’s economy; however, they continue to face various challenges, particularly in the areas of marketing, production, and financial management. This community service program was implemented at UD. Maju Bareng, an MSME engaged in the production of carica preserves, located in Karang Sari Village, Dieng Kulon, Banjarnegara. Currently, UD. Maju Bareng has not optimally utilized digital technology in conducting its business activities. Sales are still predominantly carried out through offline channels, production processes remain conventional, and financial records are maintained manually without a structured system, which has hindered business growth. The objective of this program was to enhance business capacity through the adoption of digital technology in the fields of marketing, production, and finance. The methods employed in the implementation of this community service included socialization, training, technology implementation, mentoring, and evaluation. The results indicated that the partner successfully utilized a website and online marketplaces to expand market reach, implemented simple digital-based financial recording, and increased production capacity through the addition of a cup sealer machine. The tangible impact of this program was an increase in sales turnover of 10–15%, as well as an improvement in the business owner’s digital awareness. This program demonstrates that digitalization is an effective strategy for supporting the sustainability of local MSMEs.